PERAN WAKAF DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DAN PENGEMBANGAN LEMBAGA PENDIDIKAN DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Habibulloh Habibulloh (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This study aims to determine the role of waqf in improving community welfare and the development of educational institutions in Darussalam Blokagung Banyuwangi Islamic boarding school. Waqf in Islam is one of the economic instruments for many social institutions, especially in the field of education. The problem raised about the role of waqf in the welfare of society and the development of education, this study uses a qualitative descriptive approach, where the results of the research show that waqf at the Darussalam Blokagung Islamic boarding school has been optimally managed for community empowerment. One of the strategic functions of the results of existing waqf assets is to alleviate poverty, unemployment, and community resilience through education and empowerment. Thus, the existence of this education-based waqf can indirectly improve the welfare of the community in the aspects of internalization and character building (Character Building) for students and santri so that they become knowledgeable, mature, independent and productive people. So that when they are involved in the community they can work professionally and usefully